KEBERTAHANAN PERKAWINAN IDEAL MENURUT SUKU BATAK KARO DI KELURAHAN KWALA BEKALA PADANG BULAN MEDAN - TRI SANTY BR MANALU, MELY (Humanis; Volume 2. No. 1. Januari 2013, 2013)
This study discusses the issues concerning the viability ideal marriage according tothe Batak Karo in Padang Bulan Village Kwala Bekala Medan, the formulation of theproblem as follows: 1. how the ritual of weddings and forms an ideal marriage system inthe Batak Karo? 2. Why is the ideal marriage patterns remained at Karo Batak societytoday?. The research is to be achieved are: to determine how the ideal wedding proceduresand rituals of the marriage system in Karo Batak society, to find out the ideal wedding onKaro Batak society. Above problems are analyzed using the theory of FunctionalMalinowski as the main theory and theories of social change from August Comte as thesupporting theory. While the data collection is done by collecting primary data byconducting observations and interviews, as well as the use of secondary data collectionthrough literature. The method used is descriptive-qualitative method.The results of thefield study showed that the survival of an ideal marriage according to the Batak Karo stillbe maintained where the processes and stages of marriage is very long starting from theword nungkun (apply), ngerana-ngerana (talk), maba belo sheet (woo), pemasu-masu(blessing), traditional feast and banging (uniting two hearts), Karo Batak people who livein Medan is still running